Process-based delineation of regions for a regional frequency analysis of multi-day precipitation totals in the cold season in Slovakia - GAÁL, Ladislav; SZOLGAY, Ján; LAPIN, Milan; FAŠKO, Pavol (Contributions to Geophysics and Geodesy, 2021)
Heavy multi-day precipitation totals in the cold season are studied using 35 to 53 years long series of observations from 56 climatological stations in Slovakia. Maxima of three to five-day precipitation totals in the period from October till March were chosen as data sets to be analyzed, since multi-day precipitation events in the cold season that are predominantly of frontal origin involve a considerable potential for flood risk. The selected data are processed by means of the L-moments based regional frequency analysis of Hosking and Wallis. The aim of the paper is to examine, whether it is possible to identify homogeneous regions for the regional frequency analysis based purely on subjective considerations, using knowledge about the long-term regime of precipitation in the country. Several methods of process based-delineation of geographically contiguous regions are proposed and compared. At the end, regional and at-site estimates of design values for the return periods T = 20 and 100 years, respectively, are calculated and compared for selected stations from different regions, in order to assess the order of uncertainties associated with the subjective selection of the regions.